Rapid Membrane Filtration-Epifluorescent Microscopy Technique for Direct Enumeration of Bacteria in Raw Milk - Pettipher, Graham L. (1980)
Membrane filtration and epifluorescent microscopy were used for the direct enumeration of bacteria in raw milk. Somatic cells were lysed by treatment with trypsin and Triton X-100 so that 2 ml of milk containing up to 5 × 10(6) somatic cells/ml could be filtered. The majority of the bacteria (ca. 80%) remained intact and were concentrated on the membrane. After being stained with acridine organe, the bacteria fluoresced under ultraviolet light and could easily be counted. The clump count of orange fluorescing cells on the membrane correlated well (r = 0.91) with the corresponding plate count for farm, tanker, and silo milks. Differences between counts obtained by different operators and between the membrane clump count and plate count were not significant. The technique is rapid, taking less than 25 min, inexpensive, costing less than 50 cents per sample, and is suitable for milks containing 5 × 10(3) to 5 × 10(8) bacteria per ml.